Levels, Trends, and Risk Factors for Stillbirths in the United States: 2000–2017 - Wolfson, Carrie; Qian, Jiage; Creanga, Andreea A. (American Journal of Perinatology, 2022)
Objective This study documents 2000 to 2017 trends in stillbirth rates and changes in associations between known maternal and fetal risk factors and stillbirths for 2000 to 2002 versus 2015 to 2017 in the United States.Study Design We conducted a retrospective, population-based analysis of stillbirths and live-births using national vital statistics data. We calculated annual stillbirth rates overall and by gestational age; and examined stillbirth rates by maternal age, race-ethnicity, and state for 2000 to 2002 versus 2015 to 2017. We used Chi-squared tests to examine associations between maternal and fetal risk factors separately for early (20–27 weeks) and late (28+ weeks) stillbirths compared with live-births for 2000 to 2002 versus 2015 to 2017.Results Stillbirth rates declined by 7.5% (p < 0.001) during 2000 to 2006 but remained flat at approximately 6 stillbirths per 1,000 births thereafter. Throughout 2000 to 2017, there were significant improvements in stillbirth rates at 39+ weeks nationally (p < 0.001), but rates varied greatly between and within states. Sociodemographic (advanced maternal age, Black race, low education, unmarried status, and rural residence), obstetric, and other medical factors (>3 births, use of infertility treatment, maternal obesity, diabetes, chronic hypertension, eclampsia, no prenatal care, and tobacco use) were significantly more prevalent in women with late than early stillbirths or live births. Notably, late and total stillbirth rates were approximately 30% higher for women >35 years than for women <35 years and twice as high for non-Hispanic Black than non-Hispanic White women; American Indian/Alaska Native women represented the only racial-ethnic group with significantly higher late stillbirth rates in 2015 to 2017 than in 2000 to 2002. Pregnancy and fetal factors (multiple pregnancy, male fetus, and breech presentation) were more prevalent in women with early than late stillbirths or live births.Conclusion U.S. stillbirth rates have plateaued since 2006. There are persistent differential risk profiles for early versus late stillbirths which can inform stillbirth prevention strategies (e.g., close observation of women with risk factors for stillbirth) and new research into the causes of stillbirths by gestational age.Key Points
Keywords: stillbirths; trends; risk factors; United States